Knowledge of the Stasi in the East German Literary Sphere - Jones, Sara; Windsor, Tara Talwar; Wasihun, Betiel (Boydell & Brewer, 2026)
The first book to investigate what writers, publishers, and editors knew about the Stasi and how, rethinking the relationship between knowledge, secrecy, intuition, trust, and agency under an authoritarian regime . While much scholarship has explored what the East German Ministry for State Security - the Stasi - knew about writers, publishers, editors, and others involved in the GDR's literary sphere, none has asked what these groups knew about the Stasi, how they acquired that knowledge, and how it circulated. The present book flips the approach of existing scholarship to ask those questions, thus offering an innovative approach to studying the production and circulation of literature in East Germany. It uncovers the myriad ways in which those who wrote, published, or supported literary production that was critical of the state negotiated, circumvented, and actively confronted the threat posed by surveillance and control. The study draws on original interviews, Stasi files, and writings by Uwe Kolbe, Ekkehard Maaß, Christa Moog, Gabriele Stötzer, Bernd Wagner, and Bettina Wegner, as well as works by Stefan Heym, Ralf-Günter Krolkiewicz, Günter Kunert, and Christa Wolf. The book shows that the Stasi was a kind of "public secret"-a known unknown that was positioned between revelation and concealment. It engages with theoretical frameworks drawn from anthropology, sociology, psychology, philosophy, surveillance studies and cultural studies to reconceptualize the relationship between knowledge, secrecy, intuition, trust, and agency in an authoritarian context. This book is available as Open Access under the Creative Commons license CC BY-NC-ND. SARA JONES is Professor of Languages, Cultures, and Societies at the University of Birmingham, UK. TARA TALWAR WINDSOR is Lecturer in German Studies at the University of Leeds, UK. BETIEL WASIHUN is Lecturer in Cultural and Literary Theory at the Humboldt University of Berlin, Germany.